Peran Tuan Guru dalam Penyadaran Hukum Pembayaran Nafkah ‘Iddah Perceraian di Luar Pengadilan - Abdul Hafiz Qamar; Moh. Abdun Nasir; L. Supriadi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
This research is motivated by the author's anxiety about phenomena that occur in society, namely related to fulfilling the obligation to provide an 'iddah post-divorce carried out outside the Religious Courts, primarily through the Tuan Guru's decision in Labuapi District. This research aims to analyze the distribution of 'iddah maintenance outside the court in the Labuapi District. It also tries to analyze the factors that influence the level of legal awareness of giving 'iddah maintenance to the community. Furthermore, this article tries to analyze the form and role of Tuan Guru in socializing the fulfilment of 'iddah maintenance obligations. The authors' results indicate that the distribution of 'iddah income in Labuapi District needs to be carried out correctly. This is based on the lack of public knowledge, prevailing traditions, and conflict between husband and wife, which is the cause of divorce. In addition, in this study, the authors found two active roles of Tuan Guru in the community: to provide understanding to the community and as a mediator and family law consultant.